Patients Knowledge and Practices about Disposal of Used Insulin Needles in Diabetic patients of a Tertiary Care Hospital - Arsalan Nawaz, Amna Rizvi, Maria Shireen, Usman Hafeez, Rabia Arshad, Ammara Muzahir (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Pakistan is now the 3rd country having highest diabetic population in the world. [1] Many of the diabetics are on insulin. The issue of the safe disposal of insulin syringes is an area of concern. Aim: To assess the knowledge & disposal practices of insulin needles and its relationship with the different parameters related to diabetes education. Methods: This cross-sectional study was conducted at the Services Hospital Lahore after approval of institutional review board. 363 diabetic patients, fulfilling the inclusion criteria, were approached. The patients were interviewed through a validated questionnaire. The data was stratified according to the age, gender, duration of diabetes, duration since last instructions reviewed. The chi-square test was applied. Data was analysed using SPSS 22. Results: Almost all patients 98.6% were (n=359) adult, 4(1.2%) were adolescents i.e., below 18 years of age. Mean age of study population was 49.71±13.36 years, mean weight was 67.12±13.29 kg and mean height was 160.95± 6.89 cm. Among 363 cases, 209(57.6%) were females and 154(42.4%) were males. 242(67.5%) of study population was above age of 45 years while 118(32.5%) was below the age of 45 years. Mean duration of diabetes was 95.18±54.49 months and mean duration of insulin use was 6.45±3.7 years. Among all, 332(91.5%) use syringe for injecting insulin and 31(8.5%) use pen as device for insulin. About 95% of patients discard their insulin waste into home rubbish. Among that 95% of patients who are discarding their insulin waste into household rubbish, 91% discards it after recapping of needles but 4% of them put it into rubbish without recapping. More than three fourth (82.9%) of study participants were not confident about having correct knowledge of waste disposal while small proportion of participants (17.1%) were confident of having correct knowledge. Conclusion: Unawareness about correct insulin disposal technique is much prevalent and is a major hazard for transmitting infectious diseases accidentally. Risk can be reduced by reinforcing the education.